Evidence for a Helix-Clutch Mechanism of Transmembrane Signaling in a Bacterial Chemoreceptor. Issue 19 (25th September 2016) - Ames, Peter; Hunter, Samuel; Parkinson, John S.
Abstract: The Escherichia coli Tsr protein contains a periplasmic serine-binding domain that transmits ligand occupancy information to a cytoplasmic kinase-control domain to regulate the cell's flagellar motors. The Tsr input and output domains communicate through conformational changes transmitted through a transmembrane helix (TM2), a five-residue control cable helix at the membrane-cytoplasm interface, and a four-helix HAMP bundle. Changes in serine occupancy are known to promote TM2 piston displacements in one subunit of the Tsr homodimer. We explored how such piston motions might be relayed through the control cable to reach the input AS1 helix of HAMP by constructing and characterizing mutant receptors that had one-residue insertions or deletions in the TM2-control cable segment of Tsr. TM2 deletions caused kinase-off output shifts; TM2 insertions caused kinase-on shifts. In contrast, control cable deletions caused kinase-on output, whereas insertions at the TM2-control cable junction caused kinase-off output. These findings rule out direct mechanical transmission of TM2 conformational changes to HAMP. Instead, we suggest that the Tsr control cable transmits input signals to HAMP by modulating the intensity of structural clashes between out-of-register TM2 and AS1 helices. Inward displacement of TM2 might alter the sidechain environment of control cable residues at the membrane core-headgroup interface, causing a break in the control cable helix to attenuate the register mismatch and enhance HAMP packing stability, leading to a kinase-off output response. This helix-clutch model offers a new perspective on the mechanism of transmembrane signaling in chemoreceptors. Graphical Abstract: Highlights: How do chemoreceptors transmit stimulus information across the cytoplasmic membrane? One-residue length changes in a transmembrane helix cause receptor output shifts. Similar lesions cause reversed signal outputs in the cytoplasmic control cable helix. Input signals modulate control cable helicity to elicit receptor output responses.